Safety and effectiveness of labour induction after caesarean section using balloon catheter or oxytocin - Anda-Petronela Radan; Sofia Amylidi-Mohr; Beatrix Mosimann; Cedric Simillion; Luigi Raio; Martin Mueller; Daniel Surbek (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY